2023
DOI: 10.1126/science.adh7699
|View full text |Cite
|
Sign up to set email alerts
|

Discovery of target genes and pathways at GWAS loci by pooled single-cell CRISPR screens

Abstract: Most variants associated with complex traits and diseases identified by genome-wide association studies (GWAS) map to noncoding regions of the genome with unknown effects. Using ancestrally diverse biobank-scale GWAS data, massively parallel CRISPR screens, and single cell transcriptomic and proteomic sequencing, we discovered 124 cis -target genes of 91 noncoding blood trait GWAS loci. Using precise variant insertion via base editing, we connected specific variants with gene expression… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
47
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 74 publications
(50 citation statements)
references
References 126 publications
2
47
1
Order By: Relevance
“…Furthermore, it is unclear how required H3K9me3 is for disruption of CTCF binding. A recent study demonstrated better enhancer and promoter targeting with a KRAB-dCas9-MeCP2 system than with KRAB-dCas9 alone 38 , suggesting the importance of the repressive marks. In this work we targeted TF binding motifs directly, making it plausible that steric hindrance also contributed to TF displacement from chromatin.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, it is unclear how required H3K9me3 is for disruption of CTCF binding. A recent study demonstrated better enhancer and promoter targeting with a KRAB-dCas9-MeCP2 system than with KRAB-dCas9 alone 38 , suggesting the importance of the repressive marks. In this work we targeted TF binding motifs directly, making it plausible that steric hindrance also contributed to TF displacement from chromatin.…”
Section: Discussionmentioning
confidence: 99%
“…To study pathway activity across multiple biological contexts, we aimed to perform Perturb-seq experiments in six different cancer cell lines from different tissues of origin: A549 (lung), MCF7 (breast), HT29 (colon), HAP1 (bone marrow), BxPC3 (pancreas), and K562 (bone marrow). To facilitate multiplexed gene knockdown screens, we modified each of these lines to express a CRISPR interference (CRISPRi) dCas9-KRAB-MeCP2 cassette 30,31 (Supplementary Methods). To explore different environmental signaling contexts, we exposed each cell line to five distinct stimuli representing wellestablished pathway regulators, each of which has been broadly implicated in cellular responses and disease pathogenesis.…”
Section: Scalable and Flexible Perturb-seq Across Cell Lines And Cond...mentioning
confidence: 99%
“…For example, massively parallel CRISPR screens have been used to systematically disrupt noncoding GWAS loci, coupled with single-cell transcriptomics and proteomics to understand cis and trans-acting gene regulatory networks; similar approaches could likely be applied to vascular traits. 88 As multiomics technology continues to evolve, we anticipate that single-cell CRISPR screening will increasingly be combined with epigenomic, proteomic, and metabolomic readouts to holistically probe the molecular consequences of various single and combinatorial gene perturbations.…”
Section: Experimental Approaches For Target Validation Phenotypic Scr...mentioning
confidence: 99%